2023
DOI: 10.3390/ijms24087242
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Selenium Nanoparticles against Bisphenol A-Induced Toxicity in Porcine Intestinal Epithelial Cells

Abstract: Bisphenol A (BPA) is widely used to harden plastics and polycarbonates and causes serious toxic effects in multiple organs, including the intestines. Selenium, as an essential nutrient element for humans and animals, exhibits a predominant effect in various physiological processes. Selenium nanoparticles have attracted more and more attention due to their outstanding biological activity and biosafety. We prepared chitosan-coated selenium nanoparticles (SeNPs) and further compared the protective effects, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…1 ). Previous studies showed that the protective effects of selenium nanoparticles (SeNPs) on intestinal barrier dysfunction are closely associated with ERS-related PERK-eIF2α-ATF4-CHOP signaling pathway in vitro ( Pan et al., 2023 ; Song et al., 2022b ) and in vivo ( Qiao et al., 2022 ). A mouse model with eIF2α mutations in IECs showed increased susceptibility to dextran sulfate sodium (DSS) induced and Salmonella infection-associated colitis ( Hooper et al., 2019 ).…”
Section: Ers Has a Potential Impact On Intestinal Barrier Function Vi...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Previous studies showed that the protective effects of selenium nanoparticles (SeNPs) on intestinal barrier dysfunction are closely associated with ERS-related PERK-eIF2α-ATF4-CHOP signaling pathway in vitro ( Pan et al., 2023 ; Song et al., 2022b ) and in vivo ( Qiao et al., 2022 ). A mouse model with eIF2α mutations in IECs showed increased susceptibility to dextran sulfate sodium (DSS) induced and Salmonella infection-associated colitis ( Hooper et al., 2019 ).…”
Section: Ers Has a Potential Impact On Intestinal Barrier Function Vi...mentioning
confidence: 99%
“…The ATF6/CHOP pathway may be associated with intestinal barrier dysfunction during sepsis ( Wang et al., 2022 ). Many studies have shown that inhibition of ATF6 expression can relieve ER stress and exert protective effects on the intestinal barrier function of SeNPs ( Pan et al., 2023 ), chlorogenic acid ( Song et al., 2022a ), and berberine ( Gong et al., 2022 ). These findings underscore the importance of ATF6 signaling in intestinal barrier function.…”
Section: Ers Has a Potential Impact On Intestinal Barrier Function Vi...mentioning
confidence: 99%
“…For example, a reduction in IL-2 , an elevation in IL-4 and IL-12β , and inflammatory damage caused by Pb were mitigated by Se in chicken testes [ 10 ] and hearts [ 14 ]. Se treatment alleviated bisphenol A-caused IL-6 and IL-17 elevation and inflammatory response in IPEC-J2 cells [ 15 ], as well as relieved Pb-caused IL-6 and NO increase and inflammatory response in RAW264.7 macrophages [ 13 ]. Thus, we assumed that Se has an anti-inflammatory function under Pb stress in chicken Ces and Thi through the measurement of IL-2 , IL-4 , IL-6 , IL-12β , IL-17 , INF-γ , and NO.…”
Section: Introductionmentioning
confidence: 99%